Pet ownership, type of pet and socio-emotional development of school children - Vizek-Vidović, Vlasta (Array, 1999)
The current study was designed to compare the socio-emotional characteristics of school children pet owners and children without pets and to examine whether the type of pet is a variable which can differentiate the socio-emotional development of their owners. The subjects, 425 girls and 401 boys, were students of fourth (n=265), sixth (n=295) and eighth (n=266) grade of elementary schools from the metropolitan area of Zagreb, Croatia. Socio-emotional variables assessed in the study were: child attachment to pet, child prosocial orientation, empathy, loneliness, perception of family climate and social anxiety. The data showed that 54.4% of children in the sample were pet owners (26.2% of children in the study had a dog, 9.2% had a cat, and 19.0% had some other pet). In order to answer the main research question, several analyses of variance (gender by grade by pet ownership) were computed for each criterion of socio-emotional development. Significant main effects were obtained for empathy, prosocial orientation and pet attachment, with dog owners being more empathic and prosocially oriented than non-owners, and dog owners and cat owners being more attached to their pets than owners of other kinds of pets. Additional analyses of variance were computed in order to examine the role of attachment in the socio-emotional functioning of the children. Subjects were divided in three sub-groups: non-owners, lower then average attached owners, and higher than average attached owners. Children who scored higher than average on the attachment to pets scale showed significantly higher scores on the empathy and prosocial orientation scales than non-owners and children who scored lower than average on the attachment to pets scale. It was also found that children with higher levels of attachment to pets rated their family climate significantly better than children who had lower attachment to pets.